The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ijc.31214
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and risk of recurrence and progression in non‐muscle‐invasive bladder cancer

Abstract: The association of dietary factors with urinary bladder cancer prognosis has scarcely been investigated, and results of studies conducted to date are inconsistent. We investigated whether empirically derived dietary patterns are associated with risks of recurrence and progression in non-muscle-invasive bladder cancer (NMIBC) patients. Data from 595 newly diagnosed NMIBC patients from an ongoing prospective cohort study were used to derive dietary patterns using exploratory factor analysis. Factor scores were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
2
24
1
1
Order By: Relevance
“…An intake of ≥ 1 serving of uncooked broccoli/month (mean 3.9 servings/month) was associated with a reduced risk of CSM (HR 0.43, 95% CI 0.25-0.74) and ACM (HR 0.57, 95% CI 0.39-0.83) compared to an intake of < 1 serving/month. This and two other studies reported no associations between fruit and/or vegetable consumption and recurrence, [94,96] progression, [96] or mortality [95]. Another study reported that heavy areca nut chewing (>10 nuts/day), a practice common among individuals in South Asia, may be associated with an increased risk of recurrence (HR 2.18, 95% CI 1.37-3.47) compared to non-chewing [29].…”
Section: Diet and Supplementsmentioning
confidence: 70%
“…An intake of ≥ 1 serving of uncooked broccoli/month (mean 3.9 servings/month) was associated with a reduced risk of CSM (HR 0.43, 95% CI 0.25-0.74) and ACM (HR 0.57, 95% CI 0.39-0.83) compared to an intake of < 1 serving/month. This and two other studies reported no associations between fruit and/or vegetable consumption and recurrence, [94,96] progression, [96] or mortality [95]. Another study reported that heavy areca nut chewing (>10 nuts/day), a practice common among individuals in South Asia, may be associated with an increased risk of recurrence (HR 2.18, 95% CI 1.37-3.47) compared to non-chewing [29].…”
Section: Diet and Supplementsmentioning
confidence: 70%
“…In 2008, De Stefani et al (43) found that the dietary patterns labelled as 'sweet beverages' (high loadings of coffee, tea and added sugar) and 'Western' (high loadings of red meat, fried eggs, potatoes and red wine) were directly associated with the risk of BC based on factor analysis. In addition, the negative influence of the Western diet was also observed for BC recurrence: BC patients in the highest tertile of adherence to a Western dietary pattern had a 48 % higher risk of recurrence of BC compared with patients in the lowest tertile (6) . The Western diet is especially low in fresh fruits and vegetables, but generally high in saturated fats and red and processed meats.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of overall dietary patterns related to BC has gained a lot of attention during past years (6,7) . Instead of looking at individual foods or nutrients, analysis of dietary patterns examines the effects of the overall diet, considering the inter-correlations in the consumption of various foods and nutrients.…”
mentioning
confidence: 99%
“…In a recent article, Westhoff et al provided some valuable insights on the still unclear relationship between nutrition and bladder cancer ( 7 ). The authors published the results of a large cohort study based on 595 patients with newly diagnosed non-muscle-invasive bladder cancer, who were followed-up for a median period of 66 months.…”
mentioning
confidence: 99%
“…Albeit the results of the prospective study of Westhoff et al ( 7 ) need to be confirmed in larger prospective investigations, such as the ongoing BLEND (bladder cancer, epidemiology and nutritional determinants) study ( 13 ), some clear-cut implications can be drawn. On the assumption that a healthy diet may have a putative impact in reducing the risk of development and progression of bladder cancer, as well as on lowering the risk of developing many other human disorders, a list of foods, whose consumption may be increased or reduced, can be envisaged ( Table 1 ) ( 6 , 14 - 16 ).…”
mentioning
confidence: 99%